Pengaruh Genjer (Limnocharis flava) terhadap Penurunan Biological Oxygen Demand (BOD) Limbah Industri Karet - Anny Thuraidah; Erie Indra Puspita; Neny Oktiyani (Medical Laboratory Technology Journal, 2016)
Abstract: The levels of Biological Oxygen Demand (BOD) in the waste can be reduced by utilizing water plants such as velvetleaf (Limnocharis flava) as phytoremediation. This study aims to determine the influence of the many clumps Limnocharis flava to decreased levels of effluent BOD rubber industry with a variety clump Limnocharis flava much as 1, 2, 3, 4, and 5 clumps and clumps Limnocharis flava know the number of the most influential in lowering levels of BOD. This type of research is true experimental design with one group pretest-posttest. The research material was Limnocharis flava. The result showed the levels of initial BOD rubber waste amounted to 299.5 mg / l, decreased levels of BOD of waste rubber after being treated with Limnocharis flava with a variety of clumps. Decreased levels of BOD rubber waste for each successive treatment ranging from 1, 2, 3, 4, and 5 clumps genjer ie 13.65%, 14, 52%, 15.6%, 20.94%, and 29.05%. Based on test results obtained linear regression for each treatment their effect on levels of BOD using genjer rubber waste. Treatment using Limnocharis flava much as 5 clump results BOD levels decrease the total of up to 29.05%. This value has not met the standard the maximum allowable levels of BOD. Need soaking clumps Limnocharis flava more stout and longer so that the rubber waste reduction in BOD levels in accordance with the quality standards required.